2007
DOI: 10.1021/jp073446b
|View full text |Cite
|
Sign up to set email alerts
|

Direct XPS Evidence for Charge Transfer from a Reduced Rutile TiO2(110) Surface to Au Clusters

Abstract: The electronic structures of Au clusters deposited on the stoichiometric and reduced rutile TiO 2 (110) surfaces were investigated by means of X-ray photoelectron spectroscopy. With the increasing Au thickness, the Au 4f binding energy shifts monotonically toward lower binding energy on the stoichiometric surface, essentially demonstrating a particle size effect. On the reduced surface, the Au 4f binding energy exhibits a monotonically downward shift with the increasing Au thickness below 1.5 Å, then unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
121
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(151 citation statements)
references
References 49 publications
28
121
2
Order By: Relevance
“…37 The higher Au 4f XPS BE could also be due to a final state quantum size effect. [38][39][40] Because the size of Au particles could be decreased to a quantum size by sputtering, a quantum size effect should be discussed. At lower coverages of Au on TiO 2 (110) surface prepared in an UHV condition, it has been observed that the 4f7/2 XPS peak show ~ 0.5 eV higher BE than that of metallic Au, attributed to a final state screening effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The higher Au 4f XPS BE could also be due to a final state quantum size effect. [38][39][40] Because the size of Au particles could be decreased to a quantum size by sputtering, a quantum size effect should be discussed. At lower coverages of Au on TiO 2 (110) surface prepared in an UHV condition, it has been observed that the 4f7/2 XPS peak show ~ 0.5 eV higher BE than that of metallic Au, attributed to a final state screening effect.…”
Section: Resultsmentioning
confidence: 99%
“…At lower coverages of Au on TiO 2 (110) surface prepared in an UHV condition, it has been observed that the 4f7/2 XPS peak show ~ 0.5 eV higher BE than that of metallic Au, attributed to a final state screening effect. 39,40 Jiang et al reported a XPS evidence that on reduced TiO2 (110) surface charge transfer from the oxide support to Au also play a role in the XPS BE. 40 However, for the samples prepared in solution, the 4f7/2 XPS BE exhibits at much higher position than the BE induced by final-state quantum size or charge transfer effects.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] Scanning probe methods (STM/STS) generally require conductive supports combined with ultra-high-vacuum (UHV) conditions. The…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gold containing catalysts have been extensively studied within the last two decades and are known to be suitable for alcohol oxidation [4,5]. It was shown that the catalytic properties of the Au/TiO 2 catalysts are not only affected by the morphology of the metal oxide [6] and the size of the gold particles [7], but to a considerable degree by the gold deposition process on the metal oxide substrate [8]. Slight changes of process parameters like temperature, concentration, or precipitation and aging give different Au/TiO 2 composites [6][7][8].…”
mentioning
confidence: 99%
“…It was shown that the catalytic properties of the Au/TiO 2 catalysts are not only affected by the morphology of the metal oxide [6] and the size of the gold particles [7], but to a considerable degree by the gold deposition process on the metal oxide substrate [8]. Slight changes of process parameters like temperature, concentration, or precipitation and aging give different Au/TiO 2 composites [6][7][8]. The susceptibility of the deposition process to varying reaction conditions affects the reproducibility of the synthesis and has led to partly contradicting investigations concerning the activity of the Au/TiO 2 composites [9].…”
mentioning
confidence: 99%